Hadith #3467 - Sunan Abi Dawud - Aabad bin al-Walid bin Khalid عباد بن الوليد بن خالد الغبري; Abu Sa'id al-Khudri; Atyh bin Sa'd bin Jnad'h عطية بن سعد بن جنادة; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Ziyad bin Khaythama al-Ja'fi زياد بن خيثمة الجعفي (Sunan Abi Dawud)
A man paid in advance for a palm-tree. It did not bear fruit that year. They brought their case for decision to the Prophet (ﷺ). He said: for which do you make his property lawful? He then said: Do not pay in advance for a palm-tree till they (the fruits) were clearly in good condition.
Grade: Da'if

Hadith #4280 - Sunan Abi Dawud - al-Aswad bin Sa'id al-Hmdany الأسود بن سعيد الهمداني; Jabir bin Samra; Ziyad bin Khaythama al-Ja'fi زياد بن خيثمة الجعفي; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: This religion will continue to be strong till the time of twelve caliphs. The people then uttered: Allah is more great and uproared. He then silently a word which I could not understand. So I said to my father: What did he say, father ? He said: All of them will belong to Quraish.
Grade: Sahih